A comparative handbook to the Gospel of Mark: comparisons with Pseudepigrapha, the Qumran Schrolls [sic], and Rabbinic literature - Chilton, Bruce; Bock, Darrell L.; Gurtner, Daniel M. (The New Testament Gospels in their Judaic contexts, 2010)
This handbook addresses the Judaic context of the Gospel according to Mark. Mark's text is compared to distinct categories of writings, Pseudepigrapha (together with Philo and Josephus), discoveries related to Qumran, Rabbinic Literature (as well as the Targumim), and examples of Aramaic language that reflect first-century usage